Italy : Financial Sector Assessment Program-Technical Note-Tackling Non-Performing Assets. (IMF Staff Country Reports; Country Report ;, 2020)
Banks' asset quality has substantially improved in recent years but remains well below European peers. Non-performing loans (NPLs) fell from 16 1\2 percent in 2015 to about 8.1 percent at end-June 2019, achieved mainly through Euro 145 billion of private NPL sales. This is a substantial reduction by any standard, though NPLs remain well above the 3.0 percent average of the main European Union (EU) banks as of June 2019. New NPL formation has fallen to pre-crisis levels. Provisioning coverage was 52.5 percent as of June 2019, placing Italy 7.6 percentage points above the average of the main EU banks.